Off-season high value vegetable production under low cost poly-house in Chotanagpur plateau in Jharkhand - Singh, Bhoopendra; Singh, Devi (Indian Farming, 2018)
In Jharkhand the productivity of vegetable crop is very low due todivers climate conditions and number of factors like aboitic stresses (rainfed conditions, moisture stresses during summer, poor in soil nutrient due to gravel soil) and biotic stresses (bacterial wilt of tomato and capsicum etc). The protected cultivation provides, best alternate for the regulation /modification in the above factors as per the requirement of crop to realize its maximum potential.